Use of noninvasive imaging in the management of skin cancer. Issue 2 (March 2020) - Giuffrida, Roberta; Conforti, Claudio; Di Meo, Nicola; Deinlein, Teresa; Guida, Stefania; Zalaudek, Iris
Abstract : Purpose of review: To evaluate noninvasive imaging techniques in the management of skin cancers. Recent findings: In the last decades, a wide range of noninvasive imaging methods has been developed in the field of dermatooncology with the aim to detect and assess the several structural and molecular changes that characterize skin cancer development and progression. Summary: In this review, we discuss the current and emerging applications of noninvasive imaging approaches in skin cancer management, such as digital photography, dermoscopy, ultrasound sonography, reflectance confocal microscopy, optical coherence tomography, electrical impedance techniques, Raman spectroscopy, multispectral imaging, fluorescence imaging, and multispectral optoacustic tomography.